2017
DOI: 10.1007/s11547-017-0774-2
|View full text |Cite
|
Sign up to set email alerts
|

Interventional radiology in iatrogenic ureteral leaks: case series and literature review

Abstract: Iatrogenic ureteral injuries are a dramatic complication in medical practice. Nowadays there are no universal guidelines for their management. The aim of our study was to evaluate the feasibility of the percutaneous treatment in restoring ureteral integrity in 19 patients that came to our attention. In each case retrograde stenting failed and patients were candidates for re-surgery. Our strategy consists of two phases. The first step is the nephrostomy that allows an external urinary diversion putting dry the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
2
4
0
1
Order By: Relevance
“…In the literature, it has been reported that the most affected segment in ureteral injuries is the distal third of the ureter, at a rate of 51%, followed by the proximal and middle thirds of the ureter at rates of 30% and 19%, respectively [3,11]. In our study, the most commonly affected segment was the distal third of the ureter at a rate of 79%.…”
Section: Discussionsupporting
confidence: 56%
“…In the literature, it has been reported that the most affected segment in ureteral injuries is the distal third of the ureter, at a rate of 51%, followed by the proximal and middle thirds of the ureter at rates of 30% and 19%, respectively [3,11]. In our study, the most commonly affected segment was the distal third of the ureter at a rate of 79%.…”
Section: Discussionsupporting
confidence: 56%
“…In our study, the aim of restoring the integrity of the ureter was achieved in 12/15 patients (80%), consistent with data reported in the medical literature (64.7%–100%) [ 1 , 16 , 28 ]. Balloon dilatation was required in 4/15 patients due to iatrogenic strictures, always successfully.…”
Section: Discussionsupporting
confidence: 90%
“…Postoperative diagnosis of ureteral lesions can be very challenging because clinical manifestations are often non-specific [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В своей работе мы используем мочеточниковые стенты диаметром 6F, что позволяет поддерживать естественный пассаж мочи. В исследовании Trombatore С et al мочеточниковые стенты были удалены у четырех пациентов после среднесрочного периода наблюдения 5,5 мес [23]. В нашей работе в одном случае пациенту мочеточниковый стент удален через 3 мес без признаков нарушения естественного пассажа мочи в отдаленном периоде.…”
Section: результатыunclassified